Rehabilitation of the atrophic anterior maxilla: the multidisciplinary approach - Grira, Ibtissem; Esghir, Amal; Mamlouk, Leila; Douki, Nabiha (International dental journal, 2024)
The rehabilitation of partially edentulous patients with the use of dental implants is an established treatment with high success rates. However, there are several unfavorable clinical situations that need multidisciplinary approach to achieve aesthetic results. A 34-year-old female patient presented at the department of dentistry in sahloul Hospital, Sousse, Tunisia, after being subject of a dental trauma. She had a vertical fracture of upper right canine and premolar that conducted to their extraction. Implant supported- fixed crowns were proposed for anterior rehabilitation after CBCT analysis. An orthodontic pre-surgical treatment was performed to manage sufficient vertical space for fixed crowns. After that, The surgical approach was performed, It included guided bone regeneration followed by a fully guided implants placement. The prosthetic approach started after four months of healing time through the placement of Implant screwed -Provisional crowns to optimize the emergence profile. At the end, the final crowns were screwed with aesthetic prosthetic components to achieve a satisfactory aesthetic result. Rehabilitation of the atrophic anterior maxilla is a very challenging situation. To achieve optimal results, Advanced digital technology has been increasingly used in the field of implantology, especially when applied to the anterior maxillary region by positioning implants in the desired prosthetic position. The digital surgical guide used in this case report is a personalized surgical aid designed and manufactured for implant surgery schemes, which is of great significance for implant surgery in the anterior esthetic area. Restoration of an anterior maxillary edentulous area is comprehensive providing a complex rehabilitation treatment.